(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: This study was designed to assess the level of nomophobia among students studying in Sumandeep Nursing College, Vadodara. Emphasis was put on trying to establish the relation between age, gender, course of study, family income, occupation of parents, and duration of mobile usage. The research instruments were established and data was collected from 100 nursing students from Sumandeep Nursing College. To analyze the data descriptive and inferential statistics was used with the aim of finding association between the levels of nomophobia with selected demographic variable. Aims and Objectves: The aim of this study is to find out the level of nomophobia among students at Sumandeep Nursing College, Vadodara and develop the awareness of nomophobia through an information booklet in nursing students. Material and Method: In this research study a quantitative survey approach with descriptive research design is used. The sampling technique was non probability convenient sampling used to collect the 100 samples of student. Data collection was done by administering the NMP-Q. Data was analyzed by using descriptive and inferential statistics such as chi-square test. Results: In this study, 18%were having mild nomophobia, 68% were having moderate nomophobia, and 14% were having severe nomophobia. Also the findings show that there is an association between the levels of nomophobia with certain demographic variables. Conclusion: This study has dealt with the analysis and interpretation of the data collected from 100 nursing students. Both descriptive and inferential statistics were used to analyze the data. The analysis has been recognized and presented under various sections like description of demographic variable, association between the nomophobia levels with selected demographic variables. It was found that students have 18% mild nomophobia, 68% moderate nomophobia and 14% severenomophobia. After that we gave awareness to the students through an information booklet.